Inextensible flows of biharmonic S-curves according to Sabban frame in Heisenberg group Heis - Korpinar, Talat; Turhan, Essin (Taru Publications, 2018)
In this work, we examine inextensible flows associated biharmonic curves depending to Sabban frame in Heis(3). We define the biharmonic curves with regards to their curvatures. The differential equations characterizing biharmonic curves are given in Heis(3). Additionaly, we discover equations of one parameter family of biharmonic curves in S-Heis3(2).
Keywords: Bienergy; Biharmonic curve; Heisenberg group; Inextensible flow